Análise dos genes de virulência cagA, vacA e dupA de Helicobacter pylori e associação com doenças gástrica - Silva, Lucas Luiz de Lima (2021)
Helicobacter pylori (H. pylori) is a Gram-negative bacterium associated with the development of different gastropathies. The different clinical outcomes of infection by H. pylori are the result of the parasite-host relationship, and the virulence factors produced by the different strains of H. pylori are determinant in the pathogenesis of the infection. Based on the importance of the topic, the aim of this study was to assess the prevalence of H. pylori infection; compare the Polymerase Chain Reaction (PCR) technique with the histopathological examination for the detection of the microorganism; associate the genotypes of cagA, vacA and dupA virulence with the gastropathies presented by the patients and evaluate the origin of the local circulating strains. For this, gastric tissue biopsies from 117 dyspeptic patients were collected and used for DNA extraction. The histopathological examination report of the study patients was also obtained. The screening for H. pylori infection was performed using the 16S rRNA gene (hpx) and the positive H. pylori samples were subjected to the detection and sequencing of the virulence genes vacA, cagA and dupA. The dupA gene sequences obtained from the PCR were used for phylogenetic analysis. The prevalence of H. pylori infection found in this study was 64.1%, when considering only the PCR technique and 72.3% when associated with histopathological examination. A high frequency of positive cagA strains was found (80.0%). The cagA gene was detected in all strains present in patients with severe pathologies, while the isolated vacA gene was not detected in this group. Seriously ill patients had fewer virulence genes in the infecting strain. The presence of the dupA gene in the infecting strain was not associated as a risk factor or a protective factor for gastropathies, however, in women the infection by H. pylori dupA positive, increased the chance of developing gastritis by two. In addition, molecular phylogeny demonstrated that the dupA gene isolated in this study showed homology with genes from H. pylori strains isolated from western countries. The circulating strains of H. pylori in central-western Brazil show high heterogeneity in the frequency of cagA, vacA and dupA virulence genes and the combination of several virulence factors can influence the clinical outcomes of patients.